The influence of surface grafting on the growth rate of polymer chains. Issue 2 (6th November 2015) - Kang, Chengjun; Crockett, Rowena; Spencer, Nicholas D.
Abstract : MWs of polymers synthesized simultaneously on a surface and in solution by ATRP differ, depending on the surface grafting density. Abstract : The effect of surface grafting on growth kinetics during controlled radical polymerization (CRP) was investigated by comparing the growth of polymers in solution with that on a flat silicon surface. The surface-grafted polymers were attached to the surface via a photo-cleavable initiator, which allowed the polymers to be detached by means of UV light with a wavelength that did not lead to polymer photolysis. The molecular weights of surface- and solution-grown polymers were determined by size-exclusion chromatography (SEC). It could be shown that for a series of polymers synthesized from alkyl methacrylate monomers, it was principally the grafting density that determined the ratio of the molecular weight on the surface to that in solution.